Systematic Literature Review (SLR) : Pemanfaatan Aplikasi Geogebra Dalam Pembelajaran Matematika - Suci Miranti Hakiki; Yahfizham Yahfizham (International Forum of Researchers and Lecturers, 2024)
This research aims to see how the utilization of geogebra application in learning mathematics. The method used in this research is Systematic Literature Review (SLR). The results obtained in this study are geogebra has benefits for the subject matter of algebra, building space, geometry, space analytic geometry, transformation geometry, integral, statistics, pythagorean theorem, and trigonometry. The use of geogebra allows students to be actively involved in problem solving, increase interest in learning, and expand understanding of mathematical concepts. For teachers, geogebra helps in creating interesting learning materials, visualizing mathematical concepts more clearly, and simplifying the preparation of questions